The right place: human resources and labour policies for Italy - Dafano, Fabrizio (Community Notebook. People, Education and Welfare in the Society 5.0, 2021)
This essay is taken from the text Il posto giusto; a much more extensive work, which aims to explore the humanistic dimension of the relationship between individual and organization, through the articulation of five basic dimensions: generative dimension, symbolic cultural dimension, psychosocial dimension, evaluative dimension and developmental dimension. The proposed text examines only the latter, but nevertheless contains many of the main issues related to the essence of the constitutive relationship between the individual and the organization to which they belong. Nature of knowledge, processes of learning and organizational development, motivation and evolution of the person in his professional sphere, constitute, in fact, the main aspects around which reasoning revolves. The essay, in the particular style of its author, intends to provide stimuli and ideas through a highly provocative gait at times: intelligence needs to be challenged in order not to doze off.